1996
DOI: 10.1021/ja954102e
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design of a Sulfonamide Probe for Fluorescence Anisotropy Detection of Zinc with a Carbonic Anhydrase-Based Biosensor

Abstract: Given the avid and selective metal binding properties of naturally-occurring metalloproteins, it is possible to exploit these systems in the development of novel sensors, i.e., "biosensors", for the detection of trace quantities of metal ions. Here, we exploit the high affinity of human carbonic anhydrase II (CAII) for zinc in the detection of nanomolar concentrations of this metal ion by fluorescence anisotropy using a fluorescein-derivatized arylsulfonamide probe, 4-aminosulfonyl[1-(4-N-(5-fluoresceinylthiou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 40 publications
0
51
1
Order By: Relevance
“…In a study relevant to the binding of arylsulfonamides to CA II, Krishnamurthy et al have recently reported the binding of fluorinated benzenesulfonamides (207)(208)(209)(210)(211)(212) to BCA II. 182 By constructing a quantitative structure-activity relationship (QSAR), the investigators separated the influence of fluorination of the ring on electrostatic-Lewis basicity of ArSO 2 NH − toward the Zn II cofactor and toward the hydrogen-bond network (interactions that they assumed were dependent on pK a )-and hydrophobic-contacts of the phenyl ring with the enzyme (an interaction that they assumed was dependent on log P, the logarithm of the octanol/aqueous buffer partition coefficient)-interactions (eq 22; Figure 16A).…”
Section: Brønsted Relationships Reveal the Role Of Basicity Of The Sumentioning
confidence: 99%
See 2 more Smart Citations
“…In a study relevant to the binding of arylsulfonamides to CA II, Krishnamurthy et al have recently reported the binding of fluorinated benzenesulfonamides (207)(208)(209)(210)(211)(212) to BCA II. 182 By constructing a quantitative structure-activity relationship (QSAR), the investigators separated the influence of fluorination of the ring on electrostatic-Lewis basicity of ArSO 2 NH − toward the Zn II cofactor and toward the hydrogen-bond network (interactions that they assumed were dependent on pK a )-and hydrophobic-contacts of the phenyl ring with the enzyme (an interaction that they assumed was dependent on log P, the logarithm of the octanol/aqueous buffer partition coefficient)-interactions (eq 22; Figure 16A).…”
Section: Brønsted Relationships Reveal the Role Of Basicity Of The Sumentioning
confidence: 99%
“…As mentioned previously, Krishnamurthy et al constructed a QSAR between the affinity (K d ArSO 2 NH − ) of fluorinated benzenesulfonamides (207)(208)(209)(210)(211)(212) for BCA II and pK a and log P of the ligands (eq 22; Figure 16A). 182 Assuming that the two hydrogen bonds between the enzyme and ligand were equal to one another in energy ( Figure 13B), their analysis allows the partitioning of affinity to the structural interactions of the Zn II -N bond, the hydrogen-bond network, and the hydrophobic contacts of the phenyl ring between the ligand and enzyme (Figure 18; section 10.2.4).…”
Section: Comparison Of Affinity Of Arylsulfonamides For Ca Relative Tmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, Cu 2+ , Co 2+ , Zn 2+ , Cd 2+ , and Ni 2+ have been determined at concentration down the picomolar range (Fierke and Thompson, 2001;Thompson and Jones, 1993;Mey et al, 2011) by changes in fluorescence emission (Thompson et al, 2000) and excitation wavelength ratios (Thompson et al, 2002), lifetimes (Thompson and Patchan, 1995), and anisotropy (polarization) (Elbaum et al, 1996;Thompson et al, 2000). The sensitivity, selectivity, analyte binding, kinetics and stability of the biosensors have been improved by subtle modification of the protein structure by directed mutagenesis (Kiefer et al, 1995;Hunt et al, 1999;DiTusa et al, 2001;McCall et al, 2004;Burton et al, 2000).…”
Section: Carbonic Anhydrase-based Biosensing Of Metal Ionsmentioning
confidence: 99%
“…Further development from the CA inhibitors are sulfonamide-fluorescein conjugate 14 (Elbaum et al 1996) and dapoxyl sulfonamide 15 (Thompson et al 1999). The design of 14 was achieved by an iterative structure-based procedure in which the X-ray crystal structure of the CAII-arylsulfonamide complex was determined and analyzed for the optimal attachment point of fluorescein.…”
Section: Development Of Zinc-fluorophores From the Zinc-containing Enmentioning
confidence: 99%